Agencies and Communities Participation in the Climate Change Programs - Patungan, Ellen; Martinez, Delie Jean; Nolasco, Margie; Base, Ebonie (JPAIR Multidisciplinary Research, 2019)
Metro Naga is primarily composed of Naga City and its surrounding municipalities in the province of Camarines Sur. It is located within the heart of Bicol’s largest river basin area and is considered a flood-prone region. This provides challenges to the government agencies responsible for implementing climate change programs. The study utilized the descriptive-evaluative design of mixed methods of research to evaluate the community participation in the current programs and campaigns for Disaster Risk Reduction Management (DRRM) and Climate Change Adaptation (CCA). Information was gathered through Structured questionnaires, guided interviews, and focus group discussions (FGDs) from the randomly selected respondents of the four (4) Municipalities of Metro Naga. Based on the findings of the study, community residents only participated “often” on the DRRM and CCA programs ( = 2.94) and the problems encountered in its implementation were no access to effective and applicable disaster risk financing and insurance (90%) and lack of initiative from the community to rebuild and repair the houses/buildings destroyed by the disaster (28%). As a result, continuous campaigns on community involvement in disaster risk reduction and climate change adaptation should be established. The adoption of community-based disaster risk reduction management will give opportunities to the community residents to be equipped with the skills and knowledge needed to be adaptive and disaster resilient.